Pembuatan Virtual Map Gedung P Lantai 2 dan 3 Universitas Kristen Petra dengan Oculus Rift - Winata, Ezra Christian; Budhi, Gregorius Satia; Setiabudi, Djoni Haryadi (Jurnal Infra, 2015)
Development and competition in the University of Indonesia is extremely tight. Petra Christian University is also the Universitys long-standing and well known to many people in Indonesia. Prospective students would like to see more clearly the form and facilities owned by the University. The difficulties that exist in prospective students who reside outside the island, as it requires large transportation costs if you want to visit Petra Christian University. Based on thisproblem, so in this study will be the creation of applications. This application aims to facilitate students who saw virtually Petra Christian University. Results in this application, the position and shape of the object on the building resembles the original state that existed at Petra Christian University.Barriers time of making a major factor, so it cannot make the building more in detail. The whole room labs and classrooms on the 2nd floor of the building and lecturer room in the 3rd floor already done, there are only a few sections still proceed example at the laboratory assistant room, and a small part.Disadvantages of this application, requires a computer specification high enough to run the application. This is because the memory is generated in this application can be fairly large.